Architecture and Standing Biomass of a Grassland Community - Misra, C M; Mall, P L (Annals of Arid Zone, 2016)
community architecture was studied by sociological attributes and was related with the standing live (green) biomass of a natural Dichanthium annulatum (Forsk,) Stapf. dominated grassland community during 1971-72. In rainy season (June to September) there is a great prependorance of species suggesting that the most potent factor for the growth of plants of this locality is the soil moisture condition. The statistical analysis reveals that the sociological attributes are directly related with the live (green) biomass of the community.